PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Yuliana, Lisa Ayu; Sulistyowati, Endah (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
This research aimed to examine the effect of dividend policy, debt policy, and firm size on financial performance. The dividend policy was measured by Dividend Payout Ratio (DPR), the debt policy was measured by Debt Equity Ratio (DER), the firm size was measured by Logarithm Natural (Ln) total asset (SIZE), and financial performance was measured by Return On Asset (ROA). The research was quantitative. Moreover, the data collection technique used purposive sampling. In line with that, there were 23 companies as the sample. Furthermore, the population was Food and Beverage companies listed on Indonesia Stock Exchange for 3 years (2019-2020). In total, there were 69 data. Within the data, there were 27 outliers. Therefore, only 42 data were analyzed. Additionally, the data analysis technique used multiple linear regression with SPSS 26. The research result concluded that dividend policy had a negative and insignificant effect on financial performance. In contrast, debt policy had a negative and significant effect on financial performance. On the other hand, firm size had a positive and significant effect on financial performance.